2023
DOI: 10.1002/jso.27274
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in access to robotic technology and perioperative outcomes among patients treated with radical prostatectomy

Abstract: Background Most radical prostatectomies are completed with robotic assistance. While studies have previously evaluated perioperative outcomes of robot‐assisted radical prostatectomy (RARP), this study investigates disparities in access and clinical outcomes of RARP. Study Design The National Cancer Database (NCDB) was used to identify patients who received radical prostatectomy for cancer between 2010 and 2017 with outcomes through 2018. RARP was compared to open radical prostatectomy (ORP). Odds of receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…This distinction persisted even after rigorous adjustment using two well-constructed multivariate regression models, revealing a relative 44% (95% confidence interval (CI): 30−55%) and 39% (95% CI: 24−51%) reduction in RARP utilization in the latter group, respectively. 1 These findings align with the adjusted results of a prior study by Kim et al: Based on a cohort of nearly 30 000 patients who underwent radical prostatectomy between 2006 and 2008 (comprising data from the Nationwide In patient Sample and the American Hospital Association), they observed a relative 30% reduction in RARP procedures among Medicaid-insured patients. 2 It is paramount to acknowledge that while this perspective from the USA is invaluable, its direct applicability to the health care landscape in Europe is limited-mainly due to two predominant factors: First, the density of robot-assisted surgical systems remains higher in the USA than in Europe, and second, there are distinct transatlantic disparities in health care insurance systems.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…This distinction persisted even after rigorous adjustment using two well-constructed multivariate regression models, revealing a relative 44% (95% confidence interval (CI): 30−55%) and 39% (95% CI: 24−51%) reduction in RARP utilization in the latter group, respectively. 1 These findings align with the adjusted results of a prior study by Kim et al: Based on a cohort of nearly 30 000 patients who underwent radical prostatectomy between 2006 and 2008 (comprising data from the Nationwide In patient Sample and the American Hospital Association), they observed a relative 30% reduction in RARP procedures among Medicaid-insured patients. 2 It is paramount to acknowledge that while this perspective from the USA is invaluable, its direct applicability to the health care landscape in Europe is limited-mainly due to two predominant factors: First, the density of robot-assisted surgical systems remains higher in the USA than in Europe, and second, there are distinct transatlantic disparities in health care insurance systems.…”
supporting
confidence: 87%
“…To the Editors, With great interest, we have perused the highly relevant study conducted by Logan et al 1 Utilizing data extracted from the National Cancer Database (NCDB) spanning the years 2010−2017, the authors demonstrated a significant discrepancy in the choice of primary surgical therapy among prostate cancer (PCa) patients in the United States of America (USA) in function of their insurance coverage. Notably, patients with private or Medicare insurance were significantly more likely to undergo robot-assisted radical prostatectomy (RARP) compared to those without insurance or with Medicaid coverage (84.4% vs. 75.5%, respectively; p < 0.001).…”
mentioning
confidence: 99%
“…RARP became increasingly more common over the course of the study period, from 75.6% in 2010 to 90.7% in 2017. 23 Over the last 20 years, a significant portion of urologic oncology has been performed robotically and can serve as a model for surgical oncology. This includes the surgical management of bladder cancer and renal cell carcinoma.…”
Section: Penetrance Of Robotic Prostatectomymentioning
confidence: 99%